Crystallization kinetics study of silver-doped germanium glasses - Gomes Fernandes, Roger [UNESP] (2019)
A series of germanium glasses in the systems (100-x)[40GeO 2 -30Bi 2 O 3 -20PbO-10TiO 2 ] – (x) AgCl with x = 0, 1, 3 and 5 (mol%) was prepared using the melt-quenching method and then characterized taking into account their crystallization kinetics mechanisms and microstructural analysis. Through Differential Scanning Calorimetry (DSC) performed in different linear heating rate programs, the experimental data obtained were based on non-isothermal models of phase transformation, since their versatility allows us to calculate kinetic parameters, for example, activation energy for crystallization (E c ) and Avrami index n. Thus, it is possible to obtain information on the crystallization mechanism of these glasses. Independent of the model, the values of the Avrami index for each composition are the same, considering the uncertainty attributed to them. It is safe to affirm that bulk and surface nucleation contribute to the crystallization of compositions containing 0 and 1 mol% of AgCl, whereas internal and surface crystallization with one-dimensional growth occur in samples with 3 and 5 mol% of AgCl, respectively. These results were supported by a microstructural analysis from bulk samples that underwent non-isothermal heat treatment at different temperatures according to DSC crystallization peak.